Reduced Gray Matter Volume and Increased White Matter Fractional Anisotropy in Women with Hypoactive Sexual Desire Disorder. (2nd December 2013) - Bloemers, Jos; Scholte, H. Steven; van, Kim; Goldstein, Irwin; Gerritsen, Jeroen; Olivier, Berend; Tuiten, Adriaan
Abstract Introduction Models of hypoactive sexual desire disorder (HSDD) imply altered central processing of sexual stimuli. Imaging studies have identified areas which show altered processing as compared with controls, but to date, structural neuroanatomical differences have not been described. Aim The aim of this study is to investigate differences in brain structure between women with HSDD and women with no history of sexual dysfunction, and to determine sexual behavioral correlates of identified structural deviations. Methods Sexual functioning and gray matter (GM) and white matter (WM) were assessed in 29 women with HSDD and 16 healthy control subjects of comparable age and socioeconomic status with no history of sexual dysfunction. Main Outcome Measures WM properties were measured using diffusion‐weighted imaging and analyzed using fractional anisotropy (FA). GM volume was measured using three‐dimensional T1‐weighted recordings and analyzed using voxel‐based morphometry. Sexual functioning was measured using the Sexual Function Questionnaire. Results Women with HSDD, as compared with controls, had reduced GM volume in the right insula, bilateral anterior temporal cortices, left occipitotemporal cortex, anterior cingulate gyrus, and right dorsolateral prefrontal cortex. Also, increased WM FA was observed within, amongst others, the bilateral amygdalae. Sexual interest and arousal correlated mostly with GM volume in these regions, whereas orgasm function correlated mostly with WM FA. Conclusion HSDD coincides with anatomical differences in the central nervous system, in both GM and WM. The findings suggest that decreased salience attribution to sexual stimuli, decreased perception of bodily responses and sexual emotional stimulus perception, and concomitant altered attentional mechanisms associated with sexual response induction. Bloemers J, Scholte HS, van Rooij K, Goldstein I, Gerritsen J, Olivier B, and Tuiten A. Reduced gray matter volume and increased white matter fractional anisotropy in women with hypoactive sexual desire disorder. J Sex Med 2014;11:753–767.